Profil Keterampilan Berpikir Komputasional Mahasiswa Calon Guru pada Topik Sains - Mohammad Syaiful Anwar; Hari Anggit Cahyo Wibowo (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
In the era of digital transformation and the implementation of Kurikulum Merdeka (Independent Curriculum), computational thinking has emerged as a core cognitive competence that pre-service teachers must master. The acquisition of this skill is essential to support students' scientific reasoning. This study aims to deeply uncover the computational thinking skill profiles of pre-service teachers in solving science problems, specifically on the topic of electrical phenomena. A qualitative method with a phenomenological approach was employed in this study, involving two students from STKIP Al Hikmah Surabaya as research subjects. Data were gathered through technical triangulation, comprising a 10-item essay test, cognitive activity observations, and semi-structured interviews, and were subsequently analyzed using the Miles & Huberman interactive model. The research findings revealed that the two students exhibited highly contrasting profiles. Student 1 demonstrated mature mastery across all four computational thinking indicators, with only minor errors. Conversely, Student 2 tended to be less focused, hurried, and experienced serious cognitive barriers, particularly in abstracting physical models and formulating systematic procedural steps. However, both subjects showed an identical trend of declining scores on questions requiring more complex macro-reasoning. The conclusion of this study emphasizes that weaknesses in the pillars of computational thinking lineally impact the low metacognitive skills of prospective educators. These findings potentially trigger future difficulties for pre-service teachers in designing sequential, logical, and safe science lesson plans (Modul Ajar/RPP) and student worksheets (LKPD) for elementary school-aged children.